Pengembangan Alat Evaluasi Materi Tata Surya untuk Mengukur Kemampuan Literasi Sains Siswa SMP - Salamah, Peny Nur; Rusilowati, Ani; Sarwi, Sarwi (UPEJ Unnes Physics Education Journal, 2017)
The purpose of this research is development of evaluation instrument in solar system’s matter based on scientific literacy, aimed to find out the validity, reliability, and characteristics of evaluation instrument and also the profile of students’ scientific literacy skills. This research used Research and Development model and the sampling technique used here was Simple Random Sampling. The research was conducted in Semarang State Junior High School. The result showed that evaluation instrument was valid and reliable. The value of validation in material, construction, and language are 87.5%; 80%; dan 84% and the value of reliability is 0. 825 in the first try out and 0.803 is value in the last try out. The ratio of characteristics’ test based on four categories scientific literacy is (a) science as a body of knowledge, (b) science as a way of investigating, (c) science as a way of thinking, and (d) the interaction among science, technology, and society are 35%:20%:20%:25%. The skills profile of students’ scientific literacy in SMP N 41 Semarang are good enough in category science as a body of knowledge, but quite good in else categories.